Comparison of postoperative pain in single visit endodontics using heat-treated nickel − titanium file systems - A randomized clinical trial - Priyanka Unnikrishnan; Lalitagauri Mandke; Leena Padhye (Wolters Kluwer Medknow Publications, 2023)
Aim: The aim of the present study was to compare postoperative pain in single visit endodontics using heat-treated nickel − titanium file systems (ProTaper Gold, HyFlex EDM, V Taper 2H). Methods: Sixty patients requiring endodontic treatment in vital permanent lower molars with irreversible pulpitis were included in the study. Patients were divided into three groups each containing 20 patients: Group 1 teeth prepared with ProTaper Gold (Dentsply), Group 2 HyFlex EDM (Coltene), and Group 3-V Taper 2H (SS WHITE). Treatment was performed in a single visit. The severity of the postoperative pain was assessed by the Visual Analog Scale after 2, 4, 8, 12, 24, and 48 h. Data were analyzed using the Kruskal-Wallis tests. Results: There was no significant difference in the incidence of postoperative pain among the three groups. There was significant reduction in pain from preoperative till the end of 2 days, irrespective of the file systems used. When compared between the three groups. There was no significant difference in pain scores at different time intervals. When change in pain from preoperative to different time intervals was compared, there was no significant difference between all three groups. V Taper 2H files showed increased pain scores from 4 to 12 h, however, the pain reduced thereafter till 48 h with no significant statistical difference. Conclusion: Results of this in vivo study showed that there was no significant difference in the incidence of postoperative pain among the three groups.